2001
DOI: 10.1095/biolreprod64.6.1835
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor-Like Ligands and erbB Genes in the Peri-Implantation Rabbit Uterus and Blastocyst1

Abstract: Molecular cloning of the partial cDNA coding sequences of the four erbB receptors and the epidermal growth factor (EGF)-like ligands EGF, transforming growth factor alpha (TGF), and heparin-binding EGF (HB-EGF) has provided the basis for a comprehensive analysis of the spatiotemporal expression pattern of the EGF receptor/ligand system during the peri-implantation period in the rabbit. Employing nonradioactive in situ hybridization and immunolocalization, we observed differential expression of erbB1-erbB3 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 55 publications
0
12
0
1
Order By: Relevance
“…It remains unclear which factors are the upstream stimulating molecules of SWAP-70-involved signaling pathway in primate trophoblasts during implantation. Many growth factors with tyrosine kinase receptors that are produced by uterine endometrium or embryo itself, such as epidermal growth factor, transforming growth factor alpha, insulin-like growth factor, etc have been proven by a large number of previous studies to play important roles in regulation of feto-maternal interaction and trophoblast invasion during embryonic implantation (Chia et al 1995;Klonisch et al 2001;Boomsma et al 2003). They might be the candidates that regulate trophoblast migration through Rac GTPase activated by SWAP-70.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear which factors are the upstream stimulating molecules of SWAP-70-involved signaling pathway in primate trophoblasts during implantation. Many growth factors with tyrosine kinase receptors that are produced by uterine endometrium or embryo itself, such as epidermal growth factor, transforming growth factor alpha, insulin-like growth factor, etc have been proven by a large number of previous studies to play important roles in regulation of feto-maternal interaction and trophoblast invasion during embryonic implantation (Chia et al 1995;Klonisch et al 2001;Boomsma et al 2003). They might be the candidates that regulate trophoblast migration through Rac GTPase activated by SWAP-70.…”
Section: Discussionmentioning
confidence: 99%
“…In rabbits, day 7 of pregnancy is considered the time of blastocyst attachment. HB-EGF mRNA is induced at the antimesometrial side of the uterus where the attachment reaction occurs on day 7 [38]. ErbBs exhibit differential expression patterns in trophoblast cells, but understanding roles of HB-EGF and ErbBs in rabbit endometria and embryos will require further investigation.…”
Section: Why Is Hb-egf Special In Implantation? – the Conservation Acmentioning
confidence: 99%
“…Previous studies have revealed transcripts for this growth factor in embryos of several species, including human (Klonisch et al, 2001), bovine (Chia et al, 1995;Kobayashi et al, 1994), porcine (Singh et al, 1993) and mouse (Das et al, 1991;Harada et al, 1997). EGF mRNA is rapidly down-regulated in mouse embryos (Das et al, 1991;Moller et al, 2001), suggesting that although detection in zygotes is due to internalization of maternal EGF during oogenesis, IVF-derived and cloned embryos are capable of expressing EGF independent of maternal influence (Kidder, 1992;Wiley et al, 1992).…”
Section: Figmentioning
confidence: 99%